Transitioning toward sustainable consumption at the Swedish local governance level - Axelsson, Katarina; André, Karin; Dawkins, Elena; Gerger Swartling, Åsa; Xylia, Maria (Frontiers in Sustainability, 2023)
Municipalities have a prominent role to play in the transition to the sustainable society by governing changes at the local level. This study, based on a quantitative survey of Swedish municipalities, has given us a broad perspective on barriers and enablers in Swedish municipalities’ efforts to plan, develop and implement measures for governing the transition to sustainable consumption. It finds that though a large share of municipalities in Sweden report working systematically on sustainable consumption, their potential appears to not be fully realized, limited primarily by a lack of political support and of key resources. Using a classification of municipalities belonging to certain groups, we find that municipalities characterized by having a city at their cores seem to have progressed further in their work to address sustainable consumption than municipalities characterized as more rural or as commuting municipalities near cities or towns. We identify opportunities to establish more responsive governance structures as important for addressing these issues, where interactions at multiple levels are required to achieve successful governance of Sweden’s work on sustainable consumption and address the barriers identified by this study. More support and guidance are needed to support municipalities’ work from higher governance levels. There also appears to be room for expanded collaborations between municipalities to prevent them from working in isolation, build capacity and foster greater knowledge exchange between municipality groups. This would strengthen municipalities’ ability to catalyze transformational change, which is crucial if they are to meet their own high ambitions related to sustainable consumption and help institute the changes needed to enable the fulfillment of the long-term sustainability challenges we face, such as those articulated in the Paris Agreement and the 2030 Agenda for Sustainable Development.